Pseudomonas aeruginosa-derived flagellin stimulates IL-6 and IL-8 production in human bronchial epithelial cells: A potential mechanism for progression and exacerbation of COPD. (14th September 2019) - Nakamoto, Keitaro; Watanabe, Masato; Sada, Mitsuru; Inui, Toshiya; Nakamura, Masuo; Honda, Kojiro; Wada, Hiroo; Ishii, Haruyuki; Takizawa, Hajime
Abstract: Background and purpose of the study: Pseudomonas aeruginosa commonly colonizes the airway of patients with chronic obstructive pulmonary disease (COPD) and exacerbates their symptoms. P. aeruginosa carries flagellin that stimulates toll-like receptor (TLR)-5; however, the role of flagellin in the pathogenesis of COPD remains unclear. The aim of the study was to evaluate the mechanisms of the flagellin-induced innate immune response in bronchial epithelial cells, and to assess the effects of anti-inflammatory agents for treatment.Materials and methods: We stimulated BEAS-2B cells with P. aeruginosa -derived flagellin, and assessed mRNA expression and protein secretion of interleukin (IL)-6 and IL-8. We also used mitogen-activated protein kinases (MAPK) inhibitors to assess the signaling pathways involved in flagellin stimulation, and investigated the effect of clinically available anti-inflammatory agents against flagellin-induced inflammation.Results: Flagellin promoted protein and mRNA expression of IL-6 and IL-8 in BEAS-2B cells and induced phosphorylation of p38, ERK, and JNK; p38 phosphorylation-induced IL-6 production, while IL-8 production resulted from p38 and ERK phosphorylation. Fluticasone propionate (FP) and dexamethasone (DEX) suppressed IL-6 and IL-8 production in BEAS-2B cells, but clarithromycin (CAM) failed to do so.Conclusions: P. aeruginosa -derived flagellin-induced IL-6 and IL-8 production in bronchial epithelial cells, which partially explains the mechanisms of progression and exacerbation of COPD. Corticosteroids are the most effective treatment for the suppression of flagellin-induced IL-6 and IL-8 production in the bronchial epithelial cells.